Emergent Carotid Stenting Plus Thrombectomy After Thrombolysis in Tandem Strokes: Analysis of the TITAN Registry. Issue 8 (August 2019) - Anadani, Mohammad; Spiotta, Alejandro M.; Alawieh, Ali; Turjman, Francis; Piotin, Michel; Haussen, Diogo C.; Nogueira, Raul G.; Papanagiotou, Panagiotis; Siddiqui, Adnan H.; Lapergue, Bertrand; Dorn, Franziska; Cognard, Christophe; et al.
Abstract : Background and Purpose—: Emergent carotid artery stenting plus mechanical thrombectomy is an effective treatment for acute ischemic stroke patients with tandem occlusion of the anterior circulation. However, there is limited data supporting the safety of this approach in patients treated with prior intravenous thrombolysis (IVT). We aimed to investigate the safety of emergent carotid artery stenting-mechanical thrombectomy approach in stroke patient population treated with prior IVT. Methods—: We assessed patients with acute ischemic stroke because of atherosclerotic tandem occlusion that were treated with emergent carotid artery stenting-mechanical thrombectomy approach from the multicenter observational Thrombectomy in Tandem Lesions registry. Patients were divided into 2 groups based on pretreatment IVT (IVT versus no-IVT). Intracerebral hemorrhages were classified according to the European Cooperative Acute Stroke Study II criteria. Results—: Among 205 patients included in the present study, 125 (60%) received prior IVT. Time from symptoms onset-to-groin puncture was shorter (234±100 versus 256±234 minutes; P =0.002), and heparin use was less in the IVT group (14% versus 35%; P <0.001); otherwise, there was no difference in the baseline characteristics. There was no significant difference between the IVT and no-IVT groups in the rate of symptomatic intracerebral hemorrhage (5% versus 8%; P =0.544), parenchymal hematoma type 1 to 2 (15% versus 18%; P =0.647), successful reperfusion (modified Thrombolysis in Cerebral Ischemia 2b–3), or 90-day favorable outcome (modified Rankin Scale score of 0–2 at 90 days). The 90-day all-cause mortality rate was significantly lower in the IVT group (8% versus 20%; P =0.017). After adjusting for covariates, IVT was not associated with symptomatic intracerebral hemorrhage or 90-day mortality. Conclusions—: Emergent carotid artery stenting-mechanical thrombectomy approach was not associated with an increased risk of hemorrhagic complications in tandem occlusion patients who received IVT before the intervention. Abstract : Supplemental Digital Content is available in the text.